SOME COMMENTS ABOUT Trichogramma - HALLMAN, GUY (Revista Colombiana de Entomología, 1979)
Natural populations of Trichogramma (Hymenoptera: Trichogrammatidae) haven often controlled pests in crops. Presently, in Colombia, the parasite is commercially produced for field release to control several Lepidoptera pest species. This study presents some observations about Trichogramma that could affect its commercial use. In the laboratory, Trichogramma did not parasitize eggs of Antigastra catalaunalis Duponchel (Lepidoptera: Pyralidae) on sesame foliage, although it parasitized 63% of eggs of this insect on paper. The parasites moved with difficulty over the pubescent leaf surface, flying after a few seconds without having encountered eggs of A. catalaunalis. The sticky pubescence of the tobacco plant caused the Trichogramma to become trapped as soon as they alighted. In cotton, a higher rate of parasitism has been observed in eggs of Alabama argillacea (Hubner) (Lepidoptera: Noctuidae) than in eggs of Heliothis spp. (Lepidoptera: Noctuidae). Trichogramma was found to walk more frequently over the smooth leaf surfaces, where the majority of the A. argillacea eggs are found, than over the pubescent terminals, where most of the Heliothis eggs are located. Parasitism of eggs of Heliothis virescens (Fabricius) by Trichogramma in 5 wild host-plants was inversely related to the number of sticky trichomes on the plant. The ratio of females to males was directly related to the number of Trichogramma which emerged from the egg in 6 species of host-eggs, by the following equation: H = 1,04A - 0,46; where H represents the number of females per male, and A is the number of Trichogramma emerging per egg of the host. The use of cloth in Trichogramma release in the field resulted in many of the parasites being entangled in the cloth fibers. This problem was avoided by the Use of plastic sheets or smooth leaves from the crop in which the releases were being conducted.